1987
DOI: 10.1016/0014-5793(87)81212-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipocortin inhibition of extracellular and intracellular phospholipases A2 is substrate concentration dependent

Abstract: Hydrolysis of Escherichia coli membrane phospholipids by pancreatic phospholipase A 2 was inhibited by lipocortin from human monocytes in a substrate dependent manner. Inhibition was completely overcome at substrate concentrations above 250 pM. Lipocortin also inhibited partially purified preparations of two intracellular phospholipases A 2 isolated from rat liver mitochondria and rat platelets when these enzymes were assayed at low micromolar concentrations of phosphatidylethanolamine. Inhibition gradually de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…However, subsequent studies failed to demonstrate any direct interaction between the 14-kDa PLA 2 and annexins. Instead, it was found that the in vitro inhibition of 14-kDa PLA 2 by annexins could be overcome by increasing the substrate concentrations (41,(62)(63)(64). The extent of inhibition was more closely related to the inhibitor:substrate rather than the inhibitor:enzyme ratio, and the kinetics of inhibition were not compatible with a simple competitive or noncompetitive pattern.…”
Section: P11 Interacts With and Inhibits Cytosolic Phospholipase Amentioning
confidence: 99%
“…However, subsequent studies failed to demonstrate any direct interaction between the 14-kDa PLA 2 and annexins. Instead, it was found that the in vitro inhibition of 14-kDa PLA 2 by annexins could be overcome by increasing the substrate concentrations (41,(62)(63)(64). The extent of inhibition was more closely related to the inhibitor:substrate rather than the inhibitor:enzyme ratio, and the kinetics of inhibition were not compatible with a simple competitive or noncompetitive pattern.…”
Section: P11 Interacts With and Inhibits Cytosolic Phospholipase Amentioning
confidence: 99%
“…(12,18). (ii) The intracellular class of PLA 2 is composed of a Ca 2ϩ -independent PLA 2 (iPLA 2 ) involved essentially in regulating the incorporation of AA into membrane phospholipids (19,20), and of the group IV cytosolic 85-kDa Ca 2ϩ -dependent PLA 2 (cPLA 2 ) responsible of intracellular AA release (16,20,21).…”
mentioning
confidence: 99%
“…Although PKC and annexins have some features in common, such as binding of Ca2+ and phospholipids and onto cytoskeletal elements, there are no structural similarities between them. Numerous roles have been attributed to annexins, including anti-phospholipase A, (Davidson et al, 1987 ;Aarsman et al, 1987), anti-coagulant (Funakoshi et al, 1987;Maurer-Fogy et al, 1988) and anti-inflammatory activities (Miele et al, 1988;Errasfa et al, 1989;Cirino et al, 1989). All these functions occur extracellularly but annexins are mainly intracellular proteins so that their exact function within the cell still remains a matter of debate.…”
mentioning
confidence: 99%